If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 76 + -9g = 5(-4 + 2g) 76 + -9g = (-4 * 5 + 2g * 5) 76 + -9g = (-20 + 10g) Solving 76 + -9g = -20 + 10g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-10g' to each side of the equation. 76 + -9g + -10g = -20 + 10g + -10g Combine like terms: -9g + -10g = -19g 76 + -19g = -20 + 10g + -10g Combine like terms: 10g + -10g = 0 76 + -19g = -20 + 0 76 + -19g = -20 Add '-76' to each side of the equation. 76 + -76 + -19g = -20 + -76 Combine like terms: 76 + -76 = 0 0 + -19g = -20 + -76 -19g = -20 + -76 Combine like terms: -20 + -76 = -96 -19g = -96 Divide each side by '-19'. g = 5.052631579 Simplifying g = 5.052631579
| 41/6=3/1/3c | | 1(x+5)=2x | | 6x-21+5x=18-3x+17 | | 17.9-t=t+3 | | 5/6divide4 | | 5z+3+4z=30 | | x-125=9(2x+3)-16 | | -55-4x=107+5x | | 256=40n | | 3(x-1)-x=-9 | | -27u/2v•4u/15v | | 3x+3(-6x)=0 | | 2m+19=m(28*2) | | 7n-9-5n=21 | | 6b^2+3b= | | 350=5e | | 11/2s=161/2 | | 4x+14-3x=-2-13 | | 2v-16=20 | | Y=6+2x^2 | | G=-0.1d+5.4 | | 6z+2y^2=nz | | -11=-2-x | | S+15+2+33= | | n=5.5n | | 83+6t=899 | | 5cos(3x)=5sin(6x) | | 4w+10=54 | | 35-5(y-4)=5 | | .8x-1.25=-.37 | | 4=2(3)+b | | (12m)(12m)+11m=15 |